Descemet Membrane Endothelial Keratoplasty versus Descemet Stripping Automated Endothelial Keratoplasty in Complicated Vitrectomized Eyes. (2nd September 2021) - Mimouni, Michael; Sorkin, Nir; Slomovic, Jacqueline; Kisilevsky, Eli; Mednick, Zale; Cohen, Eyal; Trinh, Tanya; Santaella, Gisella; Chan, Clara C.; Rootman, David S.; Slomovic, Allan R.
ABSTRACT: Purpose: Vitrectomized eyes pose a technical challenge when performing endothelial keratoplasty (EK). The aim of the study was to compare outcomes of Descemet membrane endothelial keratoplasty (DMEK) and Descemet stripping automated endothelial keratoplasty (DSAEK) in complex eyes undergoing pars plana vitrectomy (PPV) prior to or during surgery. Methods: This retrospective study included consecutive eyes that underwent pars plana infusion-assisted DMEK or pull-through DSAEK which underwent PPV prior to or during the EK at a tertiary center. Included were eyes with at least 1-year follow-up. The main outcome measures were best-corrected visual acuity (BCVA) and serious adverse events. Results: Fifty-two eyes (n = 52) with a mean follow-up time of 24.6 ± 7.4 months were included. Both groups were similar in terms of baseline characteristics although the DMEK group had a significantly larger proportion of Fuchs' patients ( p = .009). There was no significant difference in postoperative logMAR BCVA between groups at each visit ( p > .05 for all). There was a significantly higher proportion of overall serious adverse events (50.0% versus 15.4%, p = .02), retinal detachments (19.2% versus 0.0%, p = .05) and cystoid macular edema (23.1% versus 0.0%, p = .02) following DMEK. Graft detachment occurred more often following DMEK (53.9% versus 11.5%, p = .001) with no significant difference in rebubbling rates (23.1% versus 11.5%, p = .27). Conclusions: A significant and similar improvement in BCVA was achieved following DMEK and DSAEK in complex vitrectomized eyes. Patients should be advised regarding the higher rates of potential serious complications associated with a pars plana infusion DMEK in this situation.